Diseño arquitectónico de la Institución Educativa Inicial Cuna Jardín N.º 462 para la formación integral del alumno en el distrito Coronel Gregorio Albarracín Lanchipa – Tacna - Pilares Alejo, Beatriz Milagros (2017)
The present investigation is carried out in the area of Coronel Gregorio Albarracín Lanchipa District and reaches the proposal of an architectural design for the Initial Educational Institution Cuna - Jardín N ° 462 that will contribute to the integral formation of the student. Among the fundamental factors that affect the integral education of the student is that the infrastructure of the I.E. it is presented with serious limitations ranging from the lack of indoor and outdoor spaces for pedagogical, complementary, administrative, general service, and educational extension functions, which put educational training at serious risk. The present investigation has like general objective, to design the architectonic project of the Initial Educational Institution Cuna - Jardín N ° 462 for the integral formation of the student.